EFFECTS OF DIETARY PROBIOTIC Bacillus NP5 ON THE GROWTH PERFORMANCES OF CATFISH (Clarias sp.) - Achmad Noerkhaerin Putra; Mustahal Mustahal; Mas Bayu Syamsunarno (BIOTROPIA, 2020)
Probiotics have long been applied in aquaculture and have shown positive effects on fish and shrimp. This research aimed to evaluate the effect of probiotic Bacillus NP5 in promoting the growth of catfish (Clarias sp.). Five doses of Bacillus NP5 with three replicates were used, namely 0% probiotic (control), 0.5% probiotic, 1% probiotic, 1.5% probiotic, and 2% probiotic (g/100 g feed). The results showed that the application of probiotics in catfish feed promoted better growth performance compared to the control. Total digestibility and protease enzyme activities were significantly highest in the 1% probiotic treatment. The specific growth rate was highest in the 1% probiotic treatment (2.67 ± 0.18% day⁻¹), followed by 2% probiotic (2.63 ± 0.02% day⁻¹), 1.5% probiotic (2.42 ± 0.07% day⁻¹), 0.5% probiotic (2.29 ± 0.14% day⁻¹), and the control (1.60 ± 0.01% day⁻¹). The addition of 1% Bacillus NP5 as a probiotic in catfish feed showed the best results for protease enzyme activity, protein digestibility, total digestibility, final weight, specific growth rate, weight gain, feed efficiency, and protein efficiency ratio compared to other probiotic doses.